Real-world evidence for Pompe disease remains fragmented. Comment on “A rare partnership: patient community and industry collaboration to shape the impact of real-world evidence on the rare disease ecosystem” by Klein et al. - Michelle E. Kruijshaar; Tiffany House; Benedikt Schoser; Pascal Laforêt; Maudy T. M. Theunissen; Stephan Wenninger; Thomas Hundsberger; Jordi Diaz-Manera; Ans T. van der Ploeg; Nadine A. M. E. van der Beek (Orphanet Journal of Rare Diseases)
Abstract In a recent publication by Klein et al., the need for real-world data on rare diseases is highlighted. We strongly support this need, and the collaboration with the patient community to collect data, as promoted in this publication. Our concern, however, is that this paper may be misunderstood as suggesting that the Sanofi-run Rare Disease Registries (RDRs) are sufficient to provide the datasets needed to evaluate current and future therapies. Industry-driven registries focus on their own product(s) and, therefore, do not provide the opportunity to compare products from different companies. Today, multiple companies produce treatments for all diseases included in the RDRs. Each company will have to run its own registry for regulatory purposes. This will lead to data fragmentation, which is prohibitive of truly understanding the effects of the various treatment options for these rare diseases. Therefore, independently funded and owned registries are essential to generate real-world evidence (RWE) unrelated to specific products. We discuss options for this for Pompe disease, including the International Pompe Survey, which has collected patient-reported outcomes independently from industry since 2002. This letter aims to raise awareness of the problem of siloed data and advocate for a new way forward where independent registries provide post-marketing surveillance data.